Characterization of composting process and chemical composition of compost from recycling centers in Surabaya City, Indonesia - Haryanta, Dwi; Sa’adah, Tatuk Tojibatus; Indarwati (Jurnal Ilmiah Pertanian, 2024)
Composting serves as a pivotal strategy in waste management, alleviating the burden on final disposal sites while simultaneously providing valuable fertilizer for urban agriculture. This study aims to delineate the intricacies of the composting process and elucidate the characteristics of compost derived from recycling centers/compost houses in Surabaya City, Indonesia. Employing a qualitative descriptive approach, this research scrutinized the composting process by delving into the origins of raw materials, procedural stages, and the chemical composition of the resultant compost. The composting materials encompassed household waste, market refuse, and fall foliage. Notably, composting occurred within an open aerobic system devoid of bio-activators. Chemical analysis revealed: C/N ratio (17.10 - 19.60), C-total (17.65% - 18.10%), N-total (0.95% - 1.12%), P2O5 (0.35% - 0.51%), K2O (0.39% - 0.41%), Cu (1.65 ppm - 2.01 ppm), Pb (2.05 ppm - 3.11 ppm), Cd (0.11 ppm - 0.24 ppm), and Zn (1.02 ppm - 1.14 ppm). Physically, the compost manifested as a dark brown substance, exhibiting a soil-like softness attributable to grinding, with temperatures oscillating between 41.90 to 55.00°C. Visually, the compost appeared mature and primed for utilization based on color and texture criteria; however, indicators such as C/N ratio and temperature suggest an immature state rendering the compost unsuitable for immediate planting. To ensure optimal maturity conducive to plant growth, it is recommended that users store the compost for a minimum of one month before application, thereby fostering its maturation process.